2012
DOI: 10.1371/journal.pone.0029527
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of N-Acetylglutamate Synthase

Abstract: The urea cycle converts toxic ammonia to urea within the liver of mammals. At least 6 enzymes are required for ureagenesis, which correlates with dietary protein intake. The transcription of urea cycle genes is, at least in part, regulated by glucocorticoid and glucagon hormone signaling pathways. N-acetylglutamate synthase (NAGS) produces a unique cofactor, N-acetylglutamate (NAG), that is essential for the catalytic function of the first and rate-limiting enzyme of ureagenesis, carbamyl phosphate synthetase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 93 publications
1
45
0
Order By: Relevance
“…NAG activates the first and rate-limiting enzyme of ureagenesis, carbamyl phosphate synthetase 1 (CPS1) (Fig. 1) (Heibel et al 2012). The enzyme that produces NAG from glutamate and Coenzyme A (CoA), NAG synthase (NAGS), is allosterically inhibited by arginine in microorganisms and plants but activated in mammals (Caldovic et al 2010).…”
Section: Metabolic Regulation Of Glutamate Utilizationmentioning
confidence: 99%
“…NAG activates the first and rate-limiting enzyme of ureagenesis, carbamyl phosphate synthetase 1 (CPS1) (Fig. 1) (Heibel et al 2012). The enzyme that produces NAG from glutamate and Coenzyme A (CoA), NAG synthase (NAGS), is allosterically inhibited by arginine in microorganisms and plants but activated in mammals (Caldovic et al 2010).…”
Section: Metabolic Regulation Of Glutamate Utilizationmentioning
confidence: 99%
“…The human NAGS gene is located on chromosome 17 within band 17q21.31 and spans approximately 8.5 kb. This includes seven exons that encode a 1605 bp open reading frame, six introns, a promoter, and an enhancer located about 3 kb upstream of the transcription start sites [45,47,[49][50][51]. The mouse Nags gene is located in the syntenic region on chromosome 11.…”
Section: Transcriptional Regulation Of Urea Cycle Genes 21 Transcripmentioning
confidence: 99%
“…The mouse Nags gene is located in the syntenic region on chromosome 11. Pairwise BLAST [52] was used for comparison of the regions upstream of the NAGS genes from seven mammals including human; this analysis revealed two conserved elements, one located immediately upstream of the first exon of the NAGS gene and a putative regulatory element located about 3 kb upstream of the NAGS translation initiation site [50]. The pattern of DNA sequence conservation within the conserved region immediately upstream of the first exon of the NAGS gene suggested that it might consist of a promoter and a proximal regulatory element, which is similar to the CPS1 regulatory region that will be described in the next section.…”
Section: Transcriptional Regulation Of Urea Cycle Genes 21 Transcripmentioning
confidence: 99%
“…Correct sequence between AAV inverted repeats of the AAV2/8.TBG.mNAGS construct was verified by DNA sequencing. For the AAV2/8.NAGS.mNAGS construct the TBG promoter was replaced with the mouse Nags promoter [40]. Mouse genomic DNA was extracted following the standard protocol using DNeasy Blood and Tissue Kit, Qiagen (Valencia, CA).…”
Section: Plasmid Construction and Aav Vector Preparationmentioning
confidence: 99%